River boundaries, floods, institutional control: Bergamo, Cremona and Pavia in Modern Age (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The aim of this study is to underline the connection between the presence of rivers (and their floods) and the economy: trades, duties, agricoltural prices, fishing and fishermen, scientists were all involved with rivers and problems caused by floods. The cities of Bergamo, Cremona and Pavia, in Lombardy, are chosen as a case study.
Keywords: Bergamo; Cremona; Esondazioni; Rivers